2022
DOI: 10.3390/nitrogen3020017
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Water and Nitrogen Utilization in Crop Trees and Understory Vegetation in a Hinoki Cypress Plantation Forest in Kochi City, Southern Japan

Abstract: Age-related changes in water and nitrogen utilization of crop and understory vegetation in a hinoki cypress plantation forest were investigated from the age of 21 to 46 years in Kochi City, southern Japan. Nitrogen concentration in the leaf litter of hinoki cypress showed a decreasing trend with forest age. The leaf δ15N of hinoki cypress was related to a quadratic function and increased from the age of 21 to 26 years and then decreased to the age of 46 years. These results suggest that older hinoki cypress tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A study in Sweden suggested that the aboveground biomass increases after reducing clear cutting in the area, thus lowering the nitrogen loss from stream water (Lucas et al, 2016). The nitrogen concentration in the leaf litter of a hinoki cypress planation decreases with increasing severity of competition with understory vegetation (Inagaki et al, 2022b). In another study, loss of understory vegetation by deer browsing increased the NO 3 loss from stream water (Chiwa, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…A study in Sweden suggested that the aboveground biomass increases after reducing clear cutting in the area, thus lowering the nitrogen loss from stream water (Lucas et al, 2016). The nitrogen concentration in the leaf litter of a hinoki cypress planation decreases with increasing severity of competition with understory vegetation (Inagaki et al, 2022b). In another study, loss of understory vegetation by deer browsing increased the NO 3 loss from stream water (Chiwa, 2021).…”
Section: Discussionmentioning
confidence: 97%